Comparison of Some Chemical Parameters of a Naturally Debittered Olive (olea Europaea L.) Type With Regular Olive Varieties - Aktaş, Ayşe Burcu; Özen, Banu; Şen, İlknur; Tokatlı, Figen; Şen, İlknur; Özen, Fatma Banu; Tokatlı, Figen (Elsevier Ltd., 2014)
Some olives grown in Karaburun peninsula in the west part of Turkey and mostly coming from Erkence variety lose their bitterness while still on the tree and are called Hurma among locals. This olive type does not require further processing to remove the bitter compounds. In this study, sugar, organic acid and fatty acid profiles of Hurma, Erkence (not naturally debittered) and Gemlik (commonly consumed as table olive) olives were determined throughout 8 weeks of maturation period for two consecutive harvest seasons, and the results were analysed by principal component analysis (PCA). PCA of sugar and organic acid data revealed a differentiation in terms of harvest year but not on variety. Hurma olive is separated from others due to its fatty acid profile, and it has higher linoleic acid content compared to others. This might be an indication of increased desaturase enzyme activity for Hurma olives during natural debittering phase.
Keywords: Composition; Fatty acid; Naturally debittered; Olive; Organic acids; Principal component analysis